Sectoral effects of intellectual capital on Malaysian SME business performance / Salwa Muda and Mara Ridhuan Che Abdul Rahman. - Muda, Salwa; Che Abdul Rahman, Mara Ridhuan (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2019)
This paper seeks to estimate and analyze the influence of intellectual capital elements on firm performance on Malaysian SMEs of two sectors, service and manufacturing. The research framework proposes relationships between intellectual capital elements; human capital, structural capital and relational capital and performance. Studies on examining the effects of intellectual capital on performance are growing, however, little is known about how the effects of intellectual capital on SMEs performance differs in different sectors. Questionnaires were delivered to managers and CEOs of SMEs as key informants of the firms to gather the data. A total of 153 usable data from both sectors were analyzed using the PLS-SEM technique through the measurement model, structural model and multigroup analysis (MGA). For the direct relationship, only the effects of human capital (HC) and relational capital on performance show significant results for the full and service sample. Meanwhile, human capital (HC) and structural capital (SC) were found to have significant effects on the manufacturing sector. The multi-group analysis further indicates that the relationship between relational capital and performance differs significantly and was stronger for the service sector.